Enhanced O2+ loss at Mars due to an ambipolar electric field from electron heating. Issue 5 (7th May 2016) - Ergun, R. E.; Andersson, L. A.; Fowler, C. M.; Woodson, A. K.; Weber, T. D.; Delory, G. T.; Andrews, D. J.; Eriksson, A. I.; McEnulty, T.; Morooka, M. W.; Stewart, A. I. F.; Mahaffy, P.R.; et al.
Abstract: Recent results from the MAVEN Langmuir Probe and Waves instrument suggest higher than predicted electron temperatures ( Te ) in Mars' dayside ionosphere above 180 km in altitude. Correspondingly, measurements from Neutral Gas and Ion Mass Spectrometer indicate significant abundances of O2 + up to 500 km in altitude, suggesting that O2 + may be a principal ion loss mechanism of oxygen. In this article, we investigate the effects of the higher Te (which results from electron heating) and ion heating on ion outflow and loss. Numerical solutions show that plasma processes including ion heating and higher Te may greatly increase O2 + loss at Mars. In particular, enhanced Te in Mars' ionosphere just above the exobase creates a substantial ambipolar electric field with a potential ( e Φ) of several kB Te, which draws ions out of the region allowing for enhanced escape. With active solar wind, electron, and ion heating, direct O2 + loss could match or exceed loss via dissociative recombination of O2 + . These results suggest that direct loss of O2 + may have played a significant role in the loss of oxygen at Mars over time. Key Points: O2 + outflow at Mars is greatly enhanced by ambipolar electric field Enhanced electron temperatures result in a strong ambipolar electric field In the past, direct loss of O2 + could have exceeded that of associative recombination